Ultrasonographic measurement of cervical length versus Bishop score for prediction of successful induction of labor - Rai, Snigdha; Pande, Prabhat B.; Poudel, Sandesh; Upadhyaya, Preetam C.; Shah, Pushkal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Induction of labor is a commonly used procedure by obstetrician which denotes artificially stimulating uterine contraction and initiating labor. This study aims to compare transvaginal measurement of cervical length and Modified Bishop score for the prediction of successful labor induction. Methods: This was a prospective cross-sectional study done at Paropakar maternity and Women’s Hospital, Kathmandu, Nepal from September 2021 to August 2022. 274 term pregnant women admitted for induction of labor were included in the study. Transvaginal sonography and Modified Bishop scoring were done within 24 hours prior to induction. Vaginal delivery within 24 hours of labor induction was considered as successful. Results: Among 274 patients that were included in the study, 203 (74.08%) of the induced patients had vaginal delivery within 24 hours and 70 (25.9%) had induction failure. Majority of the patient belonged to the reproductive age group of 19-35 years (239, 85.9%) and most of them were primigravida 157 (56.7%). The sensitivity and specificity of transvaginal cervical length and Modified Bishop Score was 72% and 66.8% vs 24% and 85%. The overall accuracy of prediction of successful labor induction was higher for transvaginal cervical length (72% vs 35%). Conclusions: Transvaginal measurement of cervical length is more accurate in predicting success of labor induction in compared to Modified Bishop Score.